Influences of central bouquet alterations on the visual outcome in eyes receiving epiretinal membrane surgery - Brinkmann, Max Philipp; Becker, Matthias D. (Applied Sciences, 2021)
Background: Previous studies have shown that epiretinal membranes (ERMs) may be associated with abnormal outer retinal anatomy. However, long-term morphological and functional results of pars plana vitrectomy (PPV) with ERM and internal limiting membrane (ILM) peeling in eyes with central bouquet (CB) alterations have not yet been investigated. Methods: In a retrospective, consecutive study all patients underwent best corrected visual acuity (BCVA) testing and spectral domain optical coherence tomography (SD-OCT) before and after a mean of 20 months (range 3–70 months) postoperatively. CB abnormalities and ERMs were classified according to Govetto’s staging systems. Results: Of the 67 eyes, 22 (34%) showed CB abnormalities at baseline. The mean BCVA increased from 0.42 at baseline to 0.20 LogMAR at final follow-up (p < 0.001). Neither ERM stage (p = 0.06) nor CB stage (p = 0.939) at baseline were significant predictors of vision improvement following surgery. Conclusions: Our results show that baseline BCVA, but not classification of CB changes and ERM at baseline, seems to be a useful predictor for functional outcomes following PPV with ERM and ILM peeling in the long-term.